To find the resulting equation from adding the two equations in the system:
-
The original equations are:
- Equation 1: \( x + 6y = 9 \)
- Equation 2: \( -x + 2y = -15 \)
-
Now add both equations together:
\[ (x + 6y) + (-x + 2y) = 9 + (-15) \]
This simplifies to:
\[ x - x + 6y + 2y = 9 - 15 \]
Which further simplifies to:
\[ 0 + 8y = -6 \]
Thus, the resulting equation from adding these two equations is:
\[ 8y = -6 \]
So among the options you've provided, the correct choice is:
8 y = negative 6.